PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIK DAN KERJASAMA SISWA: (Studi Eksperimen terhadap Siswa Kelas 3 SDN 3 Sukaratu) - Ma’arijah Nurhamidah, Soffa; Fajar Suryaningrat, Eko; Asri Pujiasti, Dea (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2022)
The focus of this research seeks to find: (1) the effect of the course review horay learning model on students' mathematical communication skills; (2) the effect of the course review horay learning model on student cooperation; and (3) the effect of the course review horay learning model on students' mathematical communication and collaboration skills. This study uses a quantitative approach with a quasi-experimental method where the subjects are third grade students at SDN 3 Sukaratu. Based on the results of the study, it was concluded that (1) there was an effect of the course review horay learning model on students' mathematical communication skills; (2) there is no effect of the course review horay learning model on student cooperation; and (3) there is an effect of the course review horay learning model on students' mathematical communication skills and collaboration